1992
DOI: 10.1681/asn.v291405
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology and economics of recombinant human erythropoietin in end-stage renal disease

Abstract: The clinical pharmacology of human recombinant erythropoietin (epoetin) was studied in order to compare the effectiveness of various routes and dosing schedules in dialysis patients. Thirty-six patients received epoetin beta three times a week i.v. for at least 12 wk. The mean dose needed to achieve target hemoglobin was 225 +/- 36 U/kg per week (median dose, 180 U/kg per week). Twenty-eight of 36 patients who were converted to a once-a-week i.v. schedule increased their requirements to 429 +/- 50 U/kg per wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(9 citation statements)
references
References 27 publications
1
4
0
4
Order By: Relevance
“…Removal of EPO from cell cultures results in apoptosis of erythroid precursor cells [45]. Thus, therapeutically meaningful erythropoiesis requires continuous ligand: receptor-binding events that can occur if the erythropoietic protein has a pharmacokinetic profile allowing maintenance at a serum concentration above the MEC [46]. Slower clearance in vivo results in an increase in relative serum concentration compared to that of a faster-clearing molecule, and the relative concentration differences between slow and fast-clearing molecules will increase with time.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of EPO from cell cultures results in apoptosis of erythroid precursor cells [45]. Thus, therapeutically meaningful erythropoiesis requires continuous ligand: receptor-binding events that can occur if the erythropoietic protein has a pharmacokinetic profile allowing maintenance at a serum concentration above the MEC [46]. Slower clearance in vivo results in an increase in relative serum concentration compared to that of a faster-clearing molecule, and the relative concentration differences between slow and fast-clearing molecules will increase with time.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] Vários estudos de farmacocinética da AEE evidenciaram maior duração da ação utilizando a via subcutânea e a mesma eficiência, com doses 30% a 50% menores que as intravenosas. [36][37][38][39] A via subcutânea é preferencial para pacientes adultos e pediátricos em quaisquer estágios da DRC, porém, a administração intravenosa é a mais confortável para crianças em hemodiálise (HD). A via intraperitoneal não é recomendada.…”
Section: Justificativaunclassified
“…Alcorco´n, 28922 Madrid, Spain. Email: jmportoles@fhalcorcon.es the threshold effect and to avoid a decline in the blood levels of erythropoietin below those necessary for the prevention of apoptosis in the bone marrow [10].…”
Section: Pharmacokinetics Of Esasmentioning
confidence: 99%
“…route needs to be given three times a week. A number of studies have shown that reducing the dose frequency to once or twice per week actually requires a 50% increase in concentration of rHuEPO dose [7][8][9]. Indeed, when the drug is given i.v.…”
Section: Pharmacokinetics Of Esasmentioning
confidence: 99%